PROMOTING HANDICRAFT FAMILY BUSINESS THROUGH DIGITAL MARKETING TOWARDS SUSTAINABLE PERFORMANCE - Santus Kumar DEB; Muhammad Shoeb Ur RAHMAN; Shohel Md. NAFI (Geo Journal of Tourism and Geosites)
The study aims to determine the dimensions of the adoption intention of digital marketing in handicraft family businesses towards business performance, as well as technological innovation applications in the family business for sustainable development. This study examines the theoretical insights and designs a conceptual framework based on previous studies of handicraft family businesses. In so doing, 290 survey data were collected from handicraft business owners and tourists by using face-to-face interviews through a structured questionnaire with 82.85% valid response rate. Moreover, structural equation modeling (SEM) was used to analyze data and find out the causal relationship among the constructs and hypothesis testing. As per the results of the study, among the 6 hypotheses paths all were supported along wit h 24 relationship path coefficients were noteworthy. The result shows that perceived ease of use, perceived risk, perceived usefulness, social norms, perceived behavioral control, and attitude radically influence to the adoption of digital marketing in han dicraft family businesses. The results of this study will assist the research scholars through theory and theoretical foundation for family business owners in understanding and comprehending the role of digital marketing in sustainable family business performance. Similarly, the legacy of family businesses in handicrafts or small businesses can be maintained and empowered through digital marketing to boost the economy. The study is the foremost one in discovering a sustainable business strategy through the success factors of digital marketing adoption in family businesses.